The Rebel Crank: redefining street barrel organs performance practice through physical gesture transgression - Parra Cancino, Juan (2023)
This paper redefines the performance practice of street barrel organs by transcending their conventional physical gestures beyond their role as mere music reproduction machines. We propose a new understanding of these instruments by establishing a parallel with how turntables started to be considered musical instruments through hand manipulation. Collaborating with Chilean 'organilleros', we experimented with the notion of ‘physical gesture transgression’ and explored creating new sounds through various body actions. We provide a list of ‘transgressive gestures,’ proposing expansions through instrument preparation or additional gestures, and how these new gestures can be annotated alongside traditional notation for other musical instruments.
Co-authored with PhD candidate and Orpheus Visiting researcher while acting as his external adviser.
FRIS
1
Keywords: Music, Thought and Technology